Uji Aktivitas Antibakteri Formulasi Sediaan Obat Kumur Ekstrak Etanol Daun Senduduk (Melastoma malabathricum L.) Terhadap Pertumbuhan Streptococcus mutans - Ayu , Tri Indah Pagar; Nasution , Haris Munandar; Rahayu, Yayuk Putri; Nasution , Muhammad Amin (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Dental caries is a common oral health problem caused by Streptococcus mutans. Antiseptic mouthwash containing natural ingredients like senduduk leaves (Melastoma malabathricum L.) shows potential as an alternative, as it contains antimicrobial compounds (alkaloids, flavonoids, saponins, and tannins). Objective: To determine the antibacterial activity of senduduk leaf ethanol extract mouthwash against S. mutans and evaluate its physical characteristics. Methods: This experimental study included: (1) ethanol extraction of senduduk leaves using 96% ethanol maceration, (2) simplicia characterization and phytochemical screening, (3) formulation of three mouthwash concentrations (2.5%, 5%, 7.5%), (4) preparation evaluation (organoleptic properties, pH, viscosity), and (5) antibacterial activity testing using the well diffusion method. Results: The mouthwash preparation met physical criteria as a light-to-dark brown liquid with pH 6.33-6.43 and viscosity of 4.833-5.726 cps. Antibacterial tests showed dose-dependent effects, with the highest inhibition zone in the 7.5% formula (18.53 mm; strong category). Conclusion: Senduduk leaf extract shows potential as an antibacterial active ingredient in herbal mouthwash against S. mutans in vitro, though further testing (in vivo/clinical trials) is needed to validate therapeutic claims.